INDONESIAN PRINTING INDUSTRY TRENDS, CURRENT TECHNOLOGY AND FUTURE DEVELOPMENT - Adi, Susanto; Lie, Liana; Antono, Adhi (Proceeding Fakultas Ekonomi, 2013)
The objectives of this project are to introduce Indonesian Printing industry from business opportunity, trend technology and development . In this project there were 3 section of explanation also with SWOT analysis. Currently Indonesian Printing Industry was growth significantly in all sectors since the last of 10 years. Investor make many investment in this in technology and high tech printing machineery. Unforttunately the growth of technology and machinery Indonesian printing industries lack of competen human resource that expert in this industry. since Indonesian Goverment concerning in this industry, they give chance to many school and university create kind of the program that support industry, This project descibing about Indonesian Printing Industry needs development and business opportunity brieflyy. Based on the survey result, the industry needs competent human resource is fist priority. Aty Indonesia education for printing in bachelor degree or management level is rare, here education degree for printing only vocational degree (high school and diploma) which their program prepared for operator and executant. now for managerial level is highly needed in order to balance the growth of technology printing. Here we established some strategies in order to increase the quality of Indonesian Human Resource in Printing business and future development decription.keywords: printing, printing industry, human resources, printing education